Bullying in the iraqi novel “Unless Touched by Fire” by Abdul Khaliq Al-Rikabi - JAWAD, Siham Hassan (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT In this study, texts from within the novel were monitored and processed according to the requirements of the curriculum used. The research aims to shed light on a social phenomenon that is reduced by language through verbal psychology and its implications within the narrative text of the novel and to show the ugliness of bullying in all its forms. Creating an idea through bullying literary models to condemn this act through a pattern of action that aesthetically affects the recipient and then behaves in society. RESUMEN En este estudio se monitorearon los textos de la novela y  se procesaron de acuerdo con los requisitos del currículo utilizado en ella. La investigación tiene como objetivo arrojar luz sobre un fenómeno social que se reduce por el lenguaje a través de la psicología verbal y sus implicaciones dentro del texto narrativo de la novela y mostrar la fealdad del bullying en todas sus formas. Crear una idea a través de modelos literarios intimidantes para condenar este acto mediante un patrón de acción que afecte estéticamente al receptor y luego se comporte en sociedad.